2020
DOI: 10.1111/jcpt.13224
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic and non‐glycaemic efficacy of once‐weekly GLP‐1 receptor agonists in people with type 2 diabetes

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 78 publications
(254 reference statements)
0
6
0
Order By: Relevance
“… 49 , 55 Across studies and populations, Semaglutide pharmacokinetics were reported with a lengthy eradication half-life and a once-weekly subcutaneous injection of 2.4 mg for its anti-obesity activity. 44 , 52 , 56 , 57 It has shown to be slowly absorbed following subcutaneous injection with a tmax of approximately 1–3 days post-subcutaneous dose. Absolute bioavailability was estimated to be 89%.…”
Section: Methodsmentioning
confidence: 99%
“… 49 , 55 Across studies and populations, Semaglutide pharmacokinetics were reported with a lengthy eradication half-life and a once-weekly subcutaneous injection of 2.4 mg for its anti-obesity activity. 44 , 52 , 56 , 57 It has shown to be slowly absorbed following subcutaneous injection with a tmax of approximately 1–3 days post-subcutaneous dose. Absolute bioavailability was estimated to be 89%.…”
Section: Methodsmentioning
confidence: 99%
“…It has been used among CP patients with HO, with some success (weight reduction of 9-22 kg); however, until now, only with short-term use (24 months) [60,61]. The weight reduction is about 5%-10%, dependent on dose and indication (type 2 diabetes or obesity) [62,63]. Much attention is now focused on the third generation of incretin drugs-for example, tirzepatide-though not yet been launched in Europe.…”
Section: Pharmacological Treatment Of Hypothalamic Obesitymentioning
confidence: 99%
“…SGLT2is prevent the reabsorption of glucose from the filtrate in the kidney, and are associated with glycaemic control, weight loss and cardiorenal protection for patients with heart failure and chronic kidney disease 107,110 . Common side effects related to SGLT2 inhibition include genital infections (empagliflozin, dapagliflozin and ertugliflozin) and increased serum lipids (empagliflozin) 117‐120 .…”
Section: Clinical Efficacy and Safety Of Glp‐1rasmentioning
confidence: 99%
“…In these trials, once-weekly use of GLP-1RAs provided additional reductions compared with sitagliptin in HbA1c (treatment differences: À0.38% to À1.06%) and body weight (À1.07 to À4.20 kg), with semaglutide (0.5 and 1.0 mg) associated with the greatest additional improvements in HbA1c (À0.77% and À1.06%) and body weight (À2.35 and À4.20 kg). 110 Meta-analyses have provided further evidence to suggest that GLP-1RAs provide greater reductions in HbA1c, fasting blood glucose concentrations and weight than DPP4is. 61,105,111 Given that GLP-1RAs and DPP4is act through the examples in Figure 1).…”
Section: Comparison With Other Key Second-line Treatmentsmentioning
confidence: 99%